Caracterización del discurso en la interacción generada a través del uso de las aplicaciones móviles Domicilios.com y Rappi, en Cali (2019)
The present work characterizes the discourse that develops in the user - machine interaction, through the use of the mobile applications Domicilios.com and Rappi, in the city of Cali. The rise in the use of digital devices, added to the constant development of Apps, represent a social and cultural phenomenon. Hence, the research starts from the communicative act user - machine / platform, since this was previously carried out human to human. Therefore, the need arose to evaluate the way in which the traditional discourse of the sale of services was appropriated by these applications and digitally adapted, in order to determine, identify and record features of written language, interaction and effects. about the consumer / user (physical and attitudinal). The digitalization of discourse and information, through digital devices, demand a characterization that reveals whether new forms of communication are presented, a variation of preferences or a change of contact when acquiring products and services. To comply with the above, the qualitative method was used making use of the following instruments: participatory observation, interviews with users and representatives of the applications, characterization tables of the discourse, interactivity and attitudes of the clients, in order that their results serve as precedents for future research, which address related issues within the field of communication and trade